Photoprotective implications of leaf variegation in E. dens-canis L. and P. officinalis L - Esteban, Raquel (Journal of plant physiology, 2008)
Variegated leaves occur rarely in nature, but there are some species, primarily in the forest understory, that possess this characteristic. We recently studied two variegated plants: Erytronium dens-canis L., which is characterised by a pattern of red patches and Pulmonaria officinalis L., with light green spots. These non-green areas could attenuate light reaching mesophyll cells with respect to green sections. The aim of the study was to verify whether such red and light green parts are more photoprotected than green ones and if this trait could be of adaptive value. Red patches in E. dens-canis were due to a single layer of red cells in the upper parenchyma, which accumulated anthocyanins. Light green spots in P. officinalis were caused by the presence of loosely arranged cells instead of a well-established layer of packed cells in the palisade parenchyma. Chlorophyll fluorescence imaging was performed under light treatment, showing a greater decrease of photochemical efficiency in red and light green patches than in green sections. Differences in the extent of photochemical efficiency among patches were not attributable to different activation of the xanthophyll cycle. These observations failed to confirm our initial hypothesis, but they questioned the physiological reason for this higher sensitivity in red and light green patches of photosynthetic tissues. Chlorophyll fluorescence imaging was therefore performed in the field. The same pattern of photochemical efficiency was maintained only in E. dens-canis. The current results demonstrate that in both species the benefits of variegation, if any, are different from enhanced photosynthetic performance